Transoral incisionless fundoplication with EsophyX for gastroesophageal reflux disease: clinical efficacy is maintained up to 10 years - Testoni, Pier Alberto; Testoni, Sabrina; Distefano, Giovanni; Mazzoleni, Giorgia; Fanti, Lorella; Passaretti, Sandro (Endoscopy International Open, 2019)
Background Transoral incisionless fundoplication with EsophyX is reported to be effective in patients with gastroesophageal reflux disease in short-medium term follow-up.Aim To examine clinical outcomes up to 10 years.Methods In total, 51 procedures were performed in 50 patients. All entered a yearly clinical follow-up schedule including gastroesophageal reflux disease health-related quality-of-life questionnaires, heartburn and regurgitation scores, and daily proton pump inhibitor consumption.Results The procedure was successfully performed in 49/50 patients. Severe complications occurred in 2/51 procedures. The remaining 49 patients were re-evaluated at 2 and 3 years, 41 after 5 years, 30 after 7 years, and 14 after 10 years. Eight patients were lost to follow-up between 3 and 5 years. Seven patients who were unresponsive to endoscopic fundoplication underwent surgical fundoplication. The mean scores at 2 years were significantly lower than before the procedure and did not change substantially during the follow-up. The rates of patients who had stopped or halved antisecretive therapy 2, 3, 5, 7, and 10 years after the procedure were 86.7 %, 84.4 %, 73.5 %, 83.3 %, and 91.7 %, respectively.Conclusions Transoral incisionless fundoplication with EsophyX is an effective therapeutic option for symptomatic gastroesophageal reflux disease patients, with Hill grades I – II or hiatal hernia < 2 cm, who refuse life-long medical therapy or surgery.